1989
DOI: 10.1007/bf01968134
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations ofYersinia pseudotuberculosis infection in children

Abstract: The clinical manifestations of infection were analysed during an outbreak of 34 cases of Yersinia pseudotuberculosis serotype Ia infection. The diagnosis was based on the results of enzyme immunoassay and verified by stool culture in five cases. The first four patients were pupils from the same school, and information on any signs and symptoms of infection was obtained by questionnaire from pupils of the school. A blood sample was obtained from 101 children. Strong IgM and IgG antibody responses to Yersinia ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
1
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 25 publications
(21 reference statements)
1
25
1
2
Order By: Relevance
“…We experimentally induced deletion of the ypm gene from a superantigen-expressing Y. pseudotuberculosis: using the association of aph(3)-IIIa and sacB genes, we demonstrated that when these reporter genes were present in the ypm locus, deletion of these genes was about 250 times more frequent than when they were located in another region of the Y. pseudotuberculosis chromosome. These results indicate that unlike other superantigenic toxin genes, the Yersinia ypm genes are not associated with mobile genetic elements but are inserted in an unstable locus of the genome.Yersinia pseudotuberculosis, a microorganism causing gastrointestinal diseases and immunopathological complications such as reactive arthritis and erythema nodosum (10,47,59,60), is at present the only gram-negative bacteria known to produce a superantigenic toxin. This molecule (designated YPM for Y. pseudotuberculosis-derived mitogen) is a 14.5-kDa protein able to induce proliferation of human T lymphocytes bearing V␤3, V␤9, V␤13.1, and V␤13.2 T-cell receptor variable regions (1, 61).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We experimentally induced deletion of the ypm gene from a superantigen-expressing Y. pseudotuberculosis: using the association of aph(3)-IIIa and sacB genes, we demonstrated that when these reporter genes were present in the ypm locus, deletion of these genes was about 250 times more frequent than when they were located in another region of the Y. pseudotuberculosis chromosome. These results indicate that unlike other superantigenic toxin genes, the Yersinia ypm genes are not associated with mobile genetic elements but are inserted in an unstable locus of the genome.Yersinia pseudotuberculosis, a microorganism causing gastrointestinal diseases and immunopathological complications such as reactive arthritis and erythema nodosum (10,47,59,60), is at present the only gram-negative bacteria known to produce a superantigenic toxin. This molecule (designated YPM for Y. pseudotuberculosis-derived mitogen) is a 14.5-kDa protein able to induce proliferation of human T lymphocytes bearing V␤3, V␤9, V␤13.1, and V␤13.2 T-cell receptor variable regions (1, 61).…”
mentioning
confidence: 99%
“…Yersinia pseudotuberculosis, a microorganism causing gastrointestinal diseases and immunopathological complications such as reactive arthritis and erythema nodosum (10,47,59,60), is at present the only gram-negative bacteria known to produce a superantigenic toxin. This molecule (designated YPM for Y. pseudotuberculosis-derived mitogen) is a 14.5-kDa protein able to induce proliferation of human T lymphocytes bearing V␤3, V␤9, V␤13.1, and V␤13.2 T-cell receptor variable regions (1,61).…”
mentioning
confidence: 99%
“…The most common manifestations of Y. pseudotuberculosis infection in humans are mesenteric lymphadenitis and ileocolitis accompanied by abdominal pain and fever (7). Y. pseudotuberculosis causes mesenteric lymphadenitis and may affect the appendix tissue and mimic appendicitis (8).…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of a long-term persistence of Y. pseudotuberculosis in Peyer's patches are unknown. Immunopathological disorders such as reactive arthritis, erythema nodosum, or vasculitis during human yersiniosis might occur several months after the enteric infection (45,46). Hence, experimental infections for a longer period of time should be followed for the possible appearance of reactive arthritis or vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…Humans are commonly infected after ingestion of food or water contaminated with excreta of infected animals. Y. pseudotuberculosis causes acute ileitis and mesenteric lymphadenitis, sometimes complicated by septicemia (10, 26), but is also responsible for the occurrence of postinfection complications such as reactive arthritis and erythema nodosum (10,35,45,46). This microorganism has been suggested as one of the causative agents of Kawasaki syndrome, an acute, self-limited vasculitis affecting predominantly infants and young children (4,25,39).…”
mentioning
confidence: 99%